β-Hydroxybutyrate in Cardiovascular Diseases : A Minor Metabolite of Great Expectations - Wei, Shao; Binbin, Liu; Yuan, Wu; Zhong, Zhang; Donghai, Lin; Caihua, Huang (Frontiers in Molecular Biosciences, 2022)
Despite recent advances in therapies, cardiovascular diseases（CVDs）are still the leading cause of mortality worldwide. Previous studies have shown that metabolic perturbations in cardiac energy metabolism are closely associated with the progressions of CVDs. Expectedly, metabolic interventions can alleviate these disorders. However, effective metabolic interventions remain rarely and are worth developing. β-hydroxybutyrate (β-HB) was once known as a harmful, toxic metabolite leading to ketoacidosis in diabetes. Yet, the minor metabolite is now increasingly recognized as a multi-functional molecular in CVDs. Although the protective role of β-HB in cardiovascular disease is controversial, increasing evidence from experimental and clinical research has shown that β-HB can not only be a “super fuel” but also a signaling metabolite with beneficial effects on vascular and cardiac dysfunction. The tremendous potentials of β-HB in the treatments of CVDs have attracted many interests of researchers. This article reviews the research progress of β-HB in CVDs and provides a theoretical basis for exploiting the potentials of β-HB in cardiovascular therapies.